Implementation of Example Method in Forming Students' Wasathiyah Islamic Character - Munir, Misbahul (Universitas Al-Amien Prenduan, 2023)
This research aims to describe the implementation of example method in forming wasathiyah Islamic character of students at Madrasah Aliyah Manbaul Ulum Tangsil Wetan Wonosari Bondowoso. The approach used is a qualitative approach with a descriptive type of research. Data collection techniques used were observation, interviews and documentation. Meanwhile, technique for determining informants used was Purposive Sampling. The data analysis technique used is Miles and Huberman model, namely data collection, data reduction, data display, and drawing conclusions. Meanwhile, the data validity test used is triangulation of sources and methods. The results of the research show that school principals, teachers and education staff show, demonstrate and give examples directly to students how to act, behave and have good ethics (uswah hasanah). The implementation is that on various occasions, school principals, teachers and education staff show a friendly, gentle and polite attitude, show an attitude of mutual respect, show an attitude of kinship and closeness, show an attitude of harmony and togetherness in differences, show an attitude of nationalism, show an attitude of care and pay attention to local wisdom, and display attitudes and behavior that integrate Islamic and Indonesian values.